Influences of Education App-Assisted Teaching Technology on Learning Efficacy of Learners - Wang, Wei (International Journal of Emerging Technologies in Learning (iJET), 2022)
Abstract—This study designed a questionnaire to investigate the influences of education app-assisted teaching technology on learners’ learning efficiency. The mediating effect of learning motivation in such influences was analyzed. Research results demonstrate that Cronbach α of the designed questionnaire is 0.833, Kaiser-Meyer-Olkin (KMO) is 0.815, and Bartlett sphericity test is p=0.000<0.001, indicating good reliability and validity of the questionnaire. All four aspects (knowledge architecture (p<0.01), group collaboration (p<0.05), information integration, summary, and assessment) of education app-assisted teaching technology positively affect learning efficacy. Learning motivation has a complete mediating effect on the influence of education app-assisted teaching technology on learning efficacy. The contact duration of learners with education APP-assisted teaching technology influences learning efficacy significantly (p=0.006<0.01). Research conclusions can provide important references to facilitate higher education teachers to integrate teaching content and online teaching deeply, realize multiple assistance effects of information technology to education modes, and promote the organic integration of mobile Internet technology and higher education.